Analysis of Conflict in “ParaNorman” Movie - Chelsea Larasati Yanwar; Hilda Puspita; Gita Mutiara Hati (UNIB Press, 2022)
This research aimed to explore and describe the types of conflict that occurred in the ParaNorman Movie. This research object was the ParaNorman movie, specifically its main character Norman Babcock. The instruments consisted of observation protocol and documentation. Data collection was through eight necessary steps, namely, 1) watch the movie, 2) download the script, 3) make sure the script and the movie were in line, 4) observe the conflicts, 5) identify the conflict, 6) note the conflict resolution, 7) summarize into the table of analysis and 7) analyze and describe the data in details. This research result showed that, in the ParaNorman movie, four conflict types existed such as 1) character-vs-self, 2) character-vs-character, 3) character-vs-supernatural, 4) character-vs-society. Consequently, it could be concluded that there were 4 types of conflict in ParaNorman movie.